AKIBAT HUKUM PENERAPAN PENGATURAN SOLE LIMITED COMPANY NEGARA LAOS DI INDONESIA - Jessica Kirana Budi (Justitia et Pax, 2020)
Laos has been successful in maintaining high and relatively stable growth for 2 (two) decades.  This continuously developing country also makes Laos as 1 (one) of the 10 (ten) fastest growing economies in the world. Regarding to this, Laos has several types of business organizations in the country, one of them is a limited company. This limited company is also regulated in Indonesian law. Referring to this, it is interesting to conduct research on how the sole limited company is regulated in Laos and what are the legal consequences that will arise if the same regulation of Laos's sole limited company is applied in Indonesia. Based on above, the writer expects the research can provide additional knowledge from the law perspective. Regarding the arrangement of Laos's sole limited company and the legal consequences that could arise if Indonesia using the same concept. This research used normative legal research methods. The conclusion of this research is that a limited company in Laos can turn into a sole limited company if the shareholders are less than 2 (two) persons and can change back into a limited company if the shareholders are at least 2 (two) persons or not more than 30 (thirty) persons. Then the legal consequences are that if Indonesia is using a sole limited company, like Laos, the shareholders are personally responsible and can be sued in the District Court by authorized persons.